Major health problems and their economic impact on beef cattle under two different feedlot systems in Brazil - Malafaia, Pedro; Granato, Tiago Alvin Lima; Costa, Rogério Magnoli; de Souza, Vinícius Carneiro [UNESP]; Costa, Diogo Fleury Azevedo; Tokarnia, Carlos Hubinger (FapUNIFESP (SciELO), 2016)
ABSTRACT.-Malafaia P., Granato T.A.L., Costa R.M., Souza V.C., Costa D.F.A. & Tokarnia C.H. 2016. Major health problems and their economic impact on beef cattle under two different feedlot systems in Brazil. Pesquisa Veterinaria Brasileira 36(9):837-843. Departamento de Nutricao Animal e Pastagem, Instituto de Zootecnia, Universidade Federal Rural do Rio de Janeiro, Seropedica, RJ 23890-000, Brazil. E-mail: malafaia_ufrrj@yahoo. com. br This study aimed to describe the diagnosis of health problems and to evaluate the cost of their treatment for cattle raised in feedlots to be slaughtered or to be sold as sires for cow--calf systems. Bovine respiratory disease and digestive disorders were the main problems diagnosed in the feedlot for slaughter; the cost for treatment was high, accounting for 9.7 to 20.9 kg of live weight (LW) or the equivalent of 7 to 15% of total LW gained over the days on feed. Due to the high intake of starch-rich concentrate, rumen and fecal pH was lower, whilst rumen osmolarity and blood lactate were higher in cattle fed for slaughter. Cattle affected by digestive disorders spent on average four additional days in the feedlot. Diseases and cost of treatments were associated with lower average daily gain and considerable economic losses. Health problems commonly observed in the feedlots for slaughter were not observed in the feedlots for males to be sold as sires. The most likely reason for this observation was the more careful nutrition and prophylactic health management in sire production systems, which produce animals of much higher selling price. Results from this study suggest that health problems found in feedlots for slaughter may not only reduce animal productivity and profitability, but also the welfare of the animals. The systemic understaffing of livestock cattle workers and veterinarians in large feedlots in Brazil results in under reporting of diseases and lack to understand epidemiological context and disease prevention.
Keywords: Beef cattle; Brazil; Diseases of cattle; Feedlot systems; Sires